A theory of recommendations - Jean-Michel Benkert; Armin Schmutzler (University of Bern, Department of Economics, 2024)
This paper investigates the value of recommendations for disseminating economic information, with a focus on frictions resulting from preference heterogeneity. We consider Bayesian expected-payoff maximizers who receive non-strategic recommendations by other consumers. The paper provides conditions under which different consumer types accept these recommendations. Moreover, we assess the overall value of a recommendation system and the determinants of that value. Our analysis highlights the importance of disentangling objective information from subjective preferences when designing value-maximizing recommendation systems.
Keywords: D02; D47; D83; 330; recommendations; preference heterogeneity; optimal design